Towards a ‘catalyst activity map’ regarding the nucleation and growth of single walled carbon nanotubes - Andrew Barron (Journal of Experimental Nanoscience, 2013)
Quantification using SEM of single walled carbon nanotubes grown per unit area using a Co-Fe (50:50) catalyst system, prepared by the incorporation of the appropriate metal salts into a Spin-On Glass substrate, at 900 °C. The effects of substrate, as well as catalyst precursor concentration, were investigated. SWNT growth density is maximised with a catalyst precursor concentration associated with the formation of catalyst nanoparticles of a critical size for SWNT nucleation. Samples were subjected to secondary growth, using a range of hydrogen:methane ratios to determine the optimum precursor composition. It was found that nucleation and growth stages are optimal under different conditions. Optimum conditions for nucleation resulted in >10× increase in SWNT density. Optimization is dependent on temperature and the partial pressure of reagent gas species.